The Influence of CEO Narcissism on CSR: The Role of Family Business as a Moderating Variable - Winston, Winston; Haryanto, Hery; Suprapto, Yandi (Jurnal Riset Akuntansi dan Keuangan, 2024)
The manufacturing industry in Indonesia plays a crucial role in economic growth, but it is also a major contributor to carbon emissions. Therefore, the need for corporate social responsibility (CSR) becomes increasingly important in addressing these environmental issues. Various factors influence a company's adoption of CSR, one of which is the CEO's characteristics. This study aims to explore the impact of CEO narcissism on CSR, with a focus on how family firms can moderate this relationship. The research involves a sample of 73 manufacturing companies listed on the Indonesia Stock Exchange, covering the period from 2018 to 2022. The data was analyzed using the Ordinary Least Square (OLS) method with the help of Stata 17 software. The results indicate that CEO narcissism has a positive impact on CSR. Furthermore, the influence of family firms can also moderate the relationship between CEO narcissism and CSR.